Laut sebagai Lanskap Budaya: Integrasi Kearifan Lokal dan Ekowisata Bahari di Kepulauan Kecil Maluku - Titing, Williem Bernadus; Afdhal; Haulussy, Rais Rahman; Afdhal, Afdhal (Asosiasi Profesi Pendidik dan Peneliti Sosiologi Indonesia (AP3SI), 2025)
This article explores the integration of local wisdom and marine ecotourism within the framework of “cultural seascapes” in small island communities in Maluku, focusing on the village of Hukurila, Ambon City. The study aims to develop a holistic understanding of how the sea is socially, culturally, and spiritually perceived and managed by local communities, and how such meanings shape sustainable ecotourism development. Employing a qualitative approach with participatory ethnographic methods, the research includes in-depth interviews, participant observation, and documentation of local practices such as sasi laut, maritime rituals, and customary coastal governance. Findings reveal that the sea is not merely viewed as an economic space but as a cultural landscape embedded with local values. Local communities actively participate as agents in managing tourism, rather than being passive objects of the industry. The contextual development of the “cultural seascapes” concept offers a novel approach to understanding human–marine relationships in small island settings, integrating tourism sociology, cultural anthropology, and political ecology. This study contributes to the advancement of sociological inquiry in eastern Indonesia—an often overlooked region—and recommends strengthening local community roles and adopting interdisciplinary, culturally sensitive frameworks in maritime tourism policymaking.